Quality assurance for point-of-care testing: Ethiopia's experience - Adisu Kebede; Yenew Kebede; Adino Desale; Achamyeleh Mulugeta; Zelalem Yaregal; Atsbeha Gebreegziabxier; Yared Tedla; Clement Zeh; Gonfa Ayana (AOSIS, 2016)
No abstract available.